Evaluating the results of kidney stone treatment by ultrasound-guided percutaneous nephrolithotomy without preoperative indwelling ureteral catheter - Pham, Ngoc Hung; Le, Van Hieu; Truong, Van Can; Nguyen, Kim Tuan; Phan, Huu Quoc Viet; Nguyen, Van Quoc Anh; Truong, Minh Tuan; Hoang, Vuong Thang; Le, Nguyen Kha (Tạp chí Y Dược Huế, 2024)
Objectives: Percutaneous nephrolithotomy (PCNL) is currently considered the gold standard surgery for most patients with staghorn kidney stones and kidney stones greater than 20 mm. The objective of this study is to evaluate the results of ultrasound-guided percutaneous nephrolithotomy without preoperative indwelling ureteral catheter. Subjects and Methods: A prospective descriptive study was conducted on 37 cases of ultrasound-guided percutaneous nephrolithotomy without preoperative indwelling ureteral catheterization at the Department of Urology, Hue Central Hospital from January 2023 to March 2024. Results: The average age of the patients was 54.6 ± 13.9 years (33 - 81). Most stones were classified as Guy II (59.4%). The level of hydronephrosis before surgery is mainly of grade II and grade III with a rate of 78.4%, and the grade I hydronephrosis accounts for 21.6%. The success rate of kidney puncture was 100%, punctured mainly the middle calyx (70.2%), the average puncture time was 141.6 ± 136 seconds, in which the group with grade III hydronephrosis had the puncture time the shortest at 45 ± 43 seconds. The average surgical time was 70.3 ± 38.2 minutes. No significant complications were noted, and immediate stone clearance rate post-surgery was 83.7%, rising to 89.1% after one month. Conclusion:Ultrasound-guided percutaneous nephrolithotomy without preoperative indwelling ureteral catheter is a safe and effective method for treating kidney stones with hydronephrosis. This technique has several advantages such as high stone clearance rates, reduced surgery time and hospital stay, and minimal complications